2016
DOI: 10.1080/10402381.2016.1212955
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of cryptic invasive watermilfoil to treatment with auxinic herbicides in a large Michigan lake

Abstract: Parks, Syndell R., "Divergent responses of cryptic invasive watermilfoil to treatment with auxinic herbicides in a large Michigan Lake" (2015). Masters Theses. identification. I am also grateful to the Houghton Lake Improvement Board to allowing Houghton Lake to be used for this study as well as funding the data analysis. Funding for this study was also provided by the Michigan Economic Development Corporation for the additional funding for this study. 4 PrefaceVegetation mapping surveys are an important part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…[3] and concern has arisen that hybrid watermilfoil may respond differently to management or be more invasive than pure Eurasian [18,19]. Several studies indicate that some hybrid watermilfoil genotypes are less affected by certain commonly-used herbicides than Eurasian, including auxinic herbicides such as triclopyr and 2,4-D (2,4-dichlorophenoxy acetic acid) [18,[20][21][22] as well as fluridone [23][24][25][26]. Parks et al [21] found a greater reduction in Eurasian watermilfoil in comparison to hybrid, following treatment with auxinic herbicides, and similar results were found by Nault et al [20] following treatment with 2,4-D. Fluridone-resistant populations of hybrid watermilfoil have been confirmed in several studies [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[3] and concern has arisen that hybrid watermilfoil may respond differently to management or be more invasive than pure Eurasian [18,19]. Several studies indicate that some hybrid watermilfoil genotypes are less affected by certain commonly-used herbicides than Eurasian, including auxinic herbicides such as triclopyr and 2,4-D (2,4-dichlorophenoxy acetic acid) [18,[20][21][22] as well as fluridone [23][24][25][26]. Parks et al [21] found a greater reduction in Eurasian watermilfoil in comparison to hybrid, following treatment with auxinic herbicides, and similar results were found by Nault et al [20] following treatment with 2,4-D. Fluridone-resistant populations of hybrid watermilfoil have been confirmed in several studies [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…We accessioned DNA-sequence data and associated metadata, including geographical coordinates and PCR primers, with GenBank (Supplemental Table S1). The protocol for the analysis of restriction endonuclease recognition sites followed Parks et al [24].…”
Section: Methodsmentioning
confidence: 99%
“…Concern over HWM's invasiveness has been present in APM for over a decade Les 2002, Les andMoody 2007). HWM can be more invasive than its parent M. spicatum: The development of HWM appears to be linked to frequent 2,4-D herbicide application (Larue et al 2013), and 2,4-D has been shown to be less effective in controlling HWM than M. spicatum (Parks et al 2016). The early and frequent chemical treatment of M. spicatum in southern Wisconsin lakes may have facilitated the presence of HWM or selected for the most tolerant milfoil strains.…”
Section: Implementing Adaptive Aquatic Plant Management Strategiesmentioning
confidence: 99%